Pediatric sedation outside the operating room integrating dexmedetomidine for MRI and CT scan procedures: A systematic review - Narjes S. Alotaibi (Saudi Journal of Anaesthesia)
This systematic review evaluates the efficacy and safety of dexmedetomidine as a sedative for pediatric patients undergoing MRI and CT scans outside the operating room. A comprehensive search of databases, including PubMed, MEDLINE, and Cochrane Library, identified relevant studies. Data on sedation success rates, onset and recovery times, adverse events, dosing, administration, and hemodynamic stability were extracted and analyzed. The results indicate that dexmedetomidine has high sedation success rates and a favorable safety profile, effectively achieving the desired sedation level with minimal adverse events, primarily manageable hemodynamic changes. Onset and recovery times were generally acceptable for clinical practice, and the flexibility in administration routes and dosing highlighted its adaptability to various clinical needs and settings. Overall, dexmedetomidine is a reliable and safe sedative for pediatric patients undergoing MRI and CT scans, offering a balanced profile of efficacy and safety, and its use can be optimized based on clinical context, patient characteristics, and procedural requirements.